CANT1 mutation is also responsible for Desbuquois dysplasia, type 2 and Kim variant. Issue 1 (30th October 2010) - Furuichi, Tatsuya; Dai, Jin; Cho, Tae-Joon; Sakazume, Satoru; Ikema, Masahide; Matsui, Yoshito; Baynam, Gareth; Nagai, Toshiro; Miyake, Noriko; Matsumoto, Naomichi; Ohashi, Hirofumi; Unger, Sheila; et al.
Abstract : Background: Desbuquois dysplasia (DD) is a recessively inherited condition characterised by short stature, generalised skeletal dysplasia and advanced bone maturation. DD is both clinically and radiographically heterogeneous, and two subtypes have been distinguished based on the presence (type 1) or absence (type 2) of an accessory metacarpal bone. In addition, an apparently distinct variant without additional metacarpal bone but with short metacarpals and long phalanges (Kim variant) has been described recently. Mutations in the gene that encodes for CANT1 (calcium-activated nucleotidase 1) have been identified in a subset of patients with DD type 1. Methods: A series of 11 subjects with DD from eight families (one type 1, two type 2, five Kim variant) were examined for CANT1 mutations by direct sequencing of all coding exons and their flanking introns. Results: Eight distinct mutations were identified in seven families (one type 1, one type 2 and all 5 Kim variant): three were nonsense and five were missense. All missense mutations occurred at highly conserved amino acids in the nucleotidase conserved regions of CANT1. Measurement of nucleotidase activity in vitro showed that the missense mutations were all associated with loss-of-function. Conclusion: The clinical-radiographic spectrum produced by CANT1 mutations must be extended to include DD type 2 and Kim variant. While presence or absence of an additional metacarpal ossification centre has been used to distinguish subtypes of DD, this sign is not a distinctive criterion to predict the molecular basis in DD.